APUCEN ENCOURAGING COMMUNITY-BASED RESEARCH TO SOLVE TODAY’S CHALLENGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SINTOK, KEDAH, 7 June 2016 – The Regional Council of the AsiaPacific UniversityCommunity Engagement Network (APUCEN) is very keen to encourage CommunityBased Research where the community will work handinhand with the university to solve problems of our time.